Kinerja Kepala Sekolah Dalam Meningkatkan Mutu Tenaga Pendidik - Palupi, Retno (Yayasan Sembilan Pemuda Indonesia, 2025)
The School Principal is the highest leader in a school education institution that has the main duties as managerial, entrepreneurship development, supervision to teaching staff and education staff based on the Minister of Education and Culture Regulation of the Republic of Indonesia Number 6 Year 2018. Workload given to the Principal aims to develop schools and improve the quality of schools based on national education standards. This study aims to determine, describe and analyze the performance of School Principals in improving the quality of Educators in SMP Negeri 1 Pangkalan Lampam, Ogan Komering Ilir Regency, and to know and describe the efforts and factors that affect theperformance of School Principals in improving the quality of Educators at SMP Negeri 1 Pangkalan Lampam Ogan Komering Ilir Regenc. This is a descriptive qualitative research which is located in SMP Negeri 1 Pangkalan Lampam, Ogan Komering Ilir Regency, using data collection techniques of observation, interviews, and documentation. The results showed that. School Principals have made efforts to improve the quality of Educators through empowerment activities and school programs such as supervision, MGMP, self-evaluation (EDS), In-house training (IHT) and entrepreneurial activities intended for Educators and students. This study has a contribution to becoming an example for other school principals in improving the quality of teaching staff.